The effects of genotype and infant weight on adult plasma levels of fibrinogen, factor VII, and LDL cholesterol are additive. Issue 7 (July 1997) - Henry, J A; Bolla, M; Osmond, C; Fall, C; Barker, D J; Humphries, S E
Abstract : High circulating levels of cholesterol, particularly low density lipoprotein (LDL) cholesterol and the clotting factors fibrinogen and factor VII, are associated with increased risk of myocardial infarction. Variations in the plasma levels of these factors are determined in part by polymorphisms in the genes concerned and also by weight at 1 year (infant weight). We have looked at the possibility of interactions between these genetic factors and infant weight in a sample of 290 men and 192 women from Hertfordshire using the beta-fibrinogen G/A-455, factor VII R353Q, and ApoE polymorphisms. The rare allele frequencies of the three polymorphisms were 0.19 for beta-fibrinogen, 0.10 for factor VII, and 0.07 and 0.13 for the 2 and 4 alleles of ApoE, and these frequencies were not different in subjects of different infant weight. In this sample, the polymorphisms showed the expected effects on plasma levels of fibrinogen, factor VII, and LDL cholesterol. The A-455 allele was associated with higher fibrinogen levels but the effect was only statistically significant in women (p = 0.003). The R353 allele was associated with higher factor VII activity in both men and women (p < 0.0001 for both). The ApoE2 allele was associated with lower levels of LDL cholesterol (p = 0.03 in men, p = 0.006 in women), while the ApoE4 allele was associated with higher levels (p < 0.001 in men, not significant in women). In this sample of men and women the effect of low infant weight was only associated with significant effects on fibrinogen and LDL cholesterol in the group of men (p = 0.005 and p = 0.008 respectively). Compared with the E3E3 subjects, the LDL lowering effect of the E2 allele and the raising effect of the E4 allele was greater in those with low infant weight compared with those with high infant weight (low v high infant weight for E2: 12.7% v 9.4%; for E4 12.7% v 8.5%). Although in this sample the interactive effect did not reach statistical significance, the additive effect of ApoE genotype and low infant weight on determining plasma LDL cholesterol levels, if confirmed, may be of relevance in determining a person's future risk of atherosclerosis.